<span>ав+ас+4в+4с=а(в+с)+4(в+с)=(в+с)(а+4)
-0,4а(2а²+3)(5-3а²)</span>=-0,4а·(10а²+15-6а⁴-9а²)=-0,4а·(15+а²-6а⁴)=-6а-0,4а³+2,4а⁵
1) 0,8 · (100 - 0,04х) = 8,64
100 - 0,04х = 8,64 : 0,8
100 - 0,04х = 10,8
0,04х = 100 - 10,8
0,04х = 89,2
х = 89,2 : 0,04
х = 2230
- - - - - - - - - - - -
2) (х + 9,14) : 7,2 = 5
х + 9,14 = 5 · 7,2
х + 9,14 = 36
х = 36 - 9,14
х = 26,86
- - - - - - - - - - - -
3) ???
4) 1,2 - (х - 4) = 2
х - 4 = 1,2 - 2
х - 4 = - 0,8
х = 4 - 0,8
х = 3,2
2х+160-4х=100
-2х=-60
х=6/2
х=3
Решение задания приложено
<span>36+(17-8)?(36+17)-8
36+17-8 =36+17-8
45=45</span>